2010
DOI: 10.1063/1.3356227
|View full text |Cite
|
Sign up to set email alerts
|

Change in magnetic properties of a cold rolled and thermally aged Fe–Cu alloy

Abstract: The variation in magnetic properties of a Fe–1%Cu model alloy due to a cold rolling and a thermal aging has been evaluated to simulate the radiation damage of reactor pressure vessel of nuclear power plant. The thermal aging was conducted at 500 °C with different aging times in series. The hysteresis loops, magnetic Barkhausen noise (BN) and Vickers microhardness were measured for prestrained, strained, and thermal aged samples. The coercivity increased by a plastic strain and decreased by thermal aging, The B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As a result, Cu precipitation using thermal aging of Fe–Cu model alloys has been investigated extensively, both experimentally (Goodman et al, 1973 b ; He et al, 2010) and theoretically (Le Bouar, 2001; Shim et al, 2007). Different aspects of this precipitation process have been examined by researchers using various experimental techniques such as field ion microscopy (Goodman et al, 1973 a ; Miller et al, 1998), atom probe tomography (APT) (Pareige et al, 1993; Auger et al, 1995; Shu et al, 2018 a ; Styman et al, 2018), high-resolution transmission electron microscopy (Othen et al, 1991; Deschamps et al, 2001), magnetization measurements (Vandenbossche et al, 2007; Hauser et al, 2008; Park et al, 2010), Vicker's hardness (He et al, 2010; Cao et al, 2013), and small-angle neutron scattering (SANS) (Deschamps et al, 2001; He et al, 2010). Results from these different experimental techniques are largely in agreement with the CRP characteristics such as dimensions and number density.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Cu precipitation using thermal aging of Fe–Cu model alloys has been investigated extensively, both experimentally (Goodman et al, 1973 b ; He et al, 2010) and theoretically (Le Bouar, 2001; Shim et al, 2007). Different aspects of this precipitation process have been examined by researchers using various experimental techniques such as field ion microscopy (Goodman et al, 1973 a ; Miller et al, 1998), atom probe tomography (APT) (Pareige et al, 1993; Auger et al, 1995; Shu et al, 2018 a ; Styman et al, 2018), high-resolution transmission electron microscopy (Othen et al, 1991; Deschamps et al, 2001), magnetization measurements (Vandenbossche et al, 2007; Hauser et al, 2008; Park et al, 2010), Vicker's hardness (He et al, 2010; Cao et al, 2013), and small-angle neutron scattering (SANS) (Deschamps et al, 2001; He et al, 2010). Results from these different experimental techniques are largely in agreement with the CRP characteristics such as dimensions and number density.…”
Section: Introductionmentioning
confidence: 99%
“…However, longer aging time coarsens the CRPs leading to a reduction in their number density as shown in Table I, 15,[19][20][21] resulting in decrease in H cm and microhardness as the mean free path of domain wall and dislocation movements increases. 15,22 Additionally, the change of inclination in the major loop (i.e., susceptibility) indicates that a larger field is required for S2 and S3 samples to obtain the same magnetization as S1 and S4. That change is consistent with the fact that CRPs can hinder the movement of domain wall (S2 versus S1) and that higher CRP density is more efficient at pinning (S3 versus S4).…”
Section: Resultsmentioning
confidence: 99%
“…Park et al 22 (their Fig. 2) showed that the time at which MBN starts to increase is delayed to higher aging time in cold worked samples.…”
Section: /Mmentioning
confidence: 99%
See 1 more Smart Citation